PREDICTION OF ANTIFUNGAL ACTIVITY AND PHARMACOKINETIC PROPERTIES OF Alpinia galanga SECONDARY METABOLITES USING PASS Online, SwissADME, AND pkCSM: PREDIKSI AKTIVITAS ANTIJAMUR DAN SIFAT FARMAKOKINETIK METABOLIT SEKUNDER Alpinia galanga MENGGUNAKAN PASS Online, SwissADME, DAN pkCSM - Muliani; Mohammad Ramdani; Baiq Khairunnisa Permatasari; Gita Olipia; Efandi Gunawan; Frendy Ferdian; Muhammad Rafli Habibi Hasri; Dodi Iskandar (ROCE : Jurnal Pertanian Terapan, 2026)
Galangal (Alpinia galanga) is a medicinal plant in the family Zingiberaceae known for various biological activities, including natural antifungal properties. This study aimed to analyze the potential of galangal secondary metabolites as natural-product-based antifungal candidates using an in silico approach. The analysis was conducted using several bioinformatics platforms, including PASS Online for antifungal activity prediction, SwissADME for physicochemical properties, water solubility, bioavailability, and drug-likeness, and pkCSM for toxicity prediction. The results showed that most galangal secondary metabolites exhibited considerable antifungal activity, as indicated by their probability of activity (Pa) values. Alpha-farnesene demonstrated the highest Pa value, followed by 1'-acetoxyeugenol acetate, galanal A, galanal B, galanganol A, and galanganol B. These compounds are known to act through mechanisms involving disruption of cell membrane permeability, inhibition of metabolism, and damage to fungal cell structures. Physicochemical property analysis indicated that the majority of compounds had molecular weights below 500, topological polar surface area (TPSA) values below 140, and a bioavailability score of 0.55, suggesting good oral absorption potential. Drug-likeness analysis revealed that most compounds complied with Lipinski, Veber, Egan, Ghose, and Muegge rules, indicating their potential for development as natural drug candidates. Furthermore, toxicity predictions indicated that most compounds were non-hepatotoxic and non-mutagenic, although several phenolic compounds exhibited mild potential for toxicity at certain concentrations. Overall, the in silico analysis indicated that galangal secondary metabolites have significant potential as effective, relatively safe, natural product-based antifungal candidates. However, further studies through in vitro and in vivo testing are still required to validate the biological effectiveness and safety of these compounds.